Differential effects of antiepileptic drugs on human bone cells - Rocha, Sara (2020)
Antiepileptic drugs (AED) have been associated to in vivo deleterious consequences in bone tissue. The present work aimed to characterize the cellular and molecular effects of five different AED on human osteoclastogenesis and osteblastogenesis. It was observed that the different drugs had the ability to differentially modulate both processes, in a way dependent on the identity and dose of the AED. Shortly, valproic acid stimulated either osteoclastogenesis and osteoblastogenesis, whereas carbamazepine, gabapentin, and lamotrigine revealed an opposite behavior; topiramate elicited a decrease of osteoclast development and an increase in osteoblast differentiation. This is the first report describing the direct effects of different AED on human primary bone cells, which is a very important issue, because these drugs are usually consumed in long-term therapeutics, with acknowledged in vivo effects in bone tissue.